Konsep Badan Hukum Perhimpunan Baitul Maal Wat Tamwil (BMT) Sebagai Penguatan Hukum Ekonomi Kerakyatan - Erisa Ardika Prasada; Joni Emirzon; K.N Sofyan Hasan (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Baitul Maal wat Tamwil (BMT) was established and developed with a gradual process of legal legality, namely BMT in which its legal entity was not yet known, BMT that had not had a legal entity, and BMT that had a diverse legal entity. This writing aimed at analyzing the concept of legal strengthening of BMT in Indonesia. This type of legal research was normative legal research on legal principles and legal systematics. Based on the discussion, it was concluded that BMT could be a legal entity because it had fulfilled the requirements requested by legislation, namely the general rule of Article 1653 of the Civil Code which stated that in addition to genuine civil fellowship, the law also recognized assembly of people as legal entity, both held or recognized by the government, or the assembly was accepted as permitted, or had been established for a specific purpose that was not contrary to law or good morality. Juridical considerations for BMT institutions were legal legality for every sharia economic activity and the variety and partial legal norms of BMT.